Cytological evaluation of pericardial fluids: A 5 years experience in tertiary care center - Surekha Yadav; Meeta Singh; Pomilla Singh; Sharmana Mandal; Nita Khurana; Shyam Lata Jain (Wolters Kluwer Medknow Publications, 2019)
Background: Cytological examination of pericardial effusion fluids is important in diagnosing the etiology of underlying disease, staging, and prognosis of cancer. Aims and Objectives: (1) To study cytological evaluation of pericardial effusions in various pathological conditions in a tertiary care center. (2) To analyze their frequency and clincopathological correlation of the diagnosis. Materials and Methods: Our study was a retrospective study performed in the Department of Pathology from 1st January 2012 to 31st December 2016. The study sample included all the pericardial effusions submitted in the pathology department for cytological evaluation. Clinical details and relevant parameters correlated with clinical findings. Each fluid underwent cytospin and cytocentrifuge along with preparation of conventional smears. Results: Of 120 cases, 80% were of benign effusion and 20% were of malignant effusion. Male-to-female ratio was 1.44:1 with patient age ranging from 3 to 90 years. Conclusion: Benign effusions can been seen in younger age group and malignant ones in the older age group. The preliminary pericardial fluid analysis in resource-limited settings is the most convenient and cost-effective method for accurate diagnosis. It reduces the demand of invasive investigations and its complications. At times, it is the first test to point toward underlying malignant process thereby affecting the prognosis, survival, and treatment outcome of the patient.